Efektivitas Ekstrak Etil Asetat Biji Kakao (Theobroma Cacao L.) Terhadap Proses Penyembuhan Luka Bakar Pada Tikus Putih Jantan - Dany Nanda Pratama (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2023)
Cacao (Theobroma cacao) is one of the plants whose all parts have functional benefits for the human body. Part of the cocoa bean is reported and has been studied as useful as an antioxidant, antibacterial, anti-obesity, and as a natural dye. Various bioactive components have been found in cocoa beans, among the bioactive components found are: Phenolics, Catechins, Epicatechins, phenolic acids, protoanthocyanidins, Tannins and Flavonoids. Handling in healing burns includes preventing infection and giving the remnants of epithelial cells the opportunity to proliferate and cover the wound surface. Compounds that can be used in healing burns are catechins, tannins and flavonoids. The method used in the extraction was maceration using Ethyl Acetate solvent, the results of the extraction obtained a viscous extract of 28 grams, preparations were made in the form of an ointment using a viscous extract in 3 concentrations namely 10%, 15% and 20%. Based on the results of the study, it was found that the Ethyl Acetate Extract of cocoa beans can be effective in healing burns.